Peningkatan Ketahanan Pangan Ternak Melalui Silase dan Fermentasi Daun Singkong bagi Peternak Kambing dan Sapi di Desa Sinar Harapan - Iqbal Nurosid; Irhan Wijayanto; Laila Ditriasari; Kirana Dewi; Iqfan Insyirah Pemana; Kurnia Dini Amelia; Juliandre Lombo; Lilik Lilik; Laila Fauzila Zahera; Lia Yuliana; Liberty Liberty (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service aims to analyze the strategy for improving livestock feed security through the utilization of cassava leaves as raw material for silage and fermented feed in Sinar Harapan Village. The limitation of green forage during the dry season is a major challenge for farmers, leading to decreased livestock productivity and high production costs. Cassava leaves, which are abundant in this village, have great potential as an alternative feed but are not yet optimally utilized. Using a qualitative descriptive method that involved training and mentoring for 20 farmers, this activity focuses on processing cassava leaves into silage and fermented feed. The results of the community service show that the application of this simple technology is highly effective. Silage and fermented feed from cassava leaves successfully improved the nutritional value, such as crude protein content, and made the feed more digestible. The final products had a fresh aroma and were well-accepted by the livestock, leading to a positive impact on daily weight gain. Economically, the use of this local raw material significantly reduced additional feed costs, thereby strengthening the farmers' self-sufficiency. Strategically, this method allows farmers to store feed for the long term, ensuring year-round feed availability and supporting the sustainability of their livestock businesses.